Discovery of novel N-(5-(tert-butyl)isoxazol-3-yl)-N′-phenylurea analogs as potent FLT3 inhibitors and evaluation of their activity against acute myeloid leukemia in vitro and in vivo. Issue 15 (1st August 2015) - Xu, Ying; Wang, Ning-Yu; Song, Xue-Jiao; Lei, Qian; Ye, Ting-Hong; You, Xin-Yu; Zuo, Wei-Qiong; Xia, Yong; Zhang, Li-Dan; Yu, Luo-Ting
Graphical abstract: Abstract: FLT3 inhibitors have been explored as a viable therapy for acute myeloid leukemia (AML). However, the clinical outcomes of these FLT3 inhibitors were underwhelming except AC220. Therefore, the development of novel FLT3 inhibitors with high potency against both FLT3-WT and FLT3-ITD mutants are strongly demanded at the present time. In this study, we designed and synthesized a series of novel N -(5-( tert -butyl)isoxazol-3-yl)- N ′-phenylurea derivatives as FLT3 inhibitors. SAR studies focused on the fused rings led to the discovery of a series of compounds with high potency against FLT3-ITD-bearing MV4-11 cells and significantly inhibitory activity toward FLT3. Among these compounds, N -(5-( tert -butyl)isoxazol-3-yl)- N ′-(4-(7-methoxyimidazo[1, 2- a ]pyridin-2-yl)phenyl)urea (16i ), displayed acceptable aqueous solubility, desirable pharmacokinetic profile and high cytotoxicity selectivity against MV4-11 cells. This compound can inhibit phosphorylation of FLT3 and induce apoptosis in a concentration-dependent manner. Further in vivo antitumor studies showed that 16i led to complete tumor regression in the MV4-11 xenograft model at a dose of 60 mg/kg/d while without observable body weight loss. This study had provided us a new chemotype of FLT3 inhibitors as novel therapic candidates for AML.